2018
DOI: 10.3389/fnmol.2018.00235
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of a Selective Adenosine A2A Receptor Antagonist in the APPswe/PS1dE9 Mouse Model of Alzheimer’s Disease

Abstract: Consumption of caffeine, a non-selective adenosine A2A receptor (A2AR) antagonist, reduces the risk of developing Alzheimer’s disease (AD) and mitigates both amyloid and Tau lesions in transgenic mouse models of the disease. While short-term treatment with A2AR antagonists have been shown to alleviate cognitive deficits in mouse models of amyloidogenesis, impact of a chronic and long-term treatment on the development of amyloid burden, associated neuroinflammation and memory deficits has never been assessed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 68 publications
0
55
0
1
Order By: Relevance
“…Several studies have shown that the levels of A 2A R expression change in AD is up to five times higher than those of normal levels (Orr et al, ). Also, in vivo data from traumatic brain injury or amyloid‐based models have demonstrated a similar range of A 2A R upsurge ranging from 1.5 to 12 fold (Zhao et al, ; Orr et al, ; Faivre et al, ; Lee et al, ). One could therefore argue that the A 2A R overexpression reached in our study is beyond the changes found in pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies have shown that the levels of A 2A R expression change in AD is up to five times higher than those of normal levels (Orr et al, ). Also, in vivo data from traumatic brain injury or amyloid‐based models have demonstrated a similar range of A 2A R upsurge ranging from 1.5 to 12 fold (Zhao et al, ; Orr et al, ; Faivre et al, ; Lee et al, ). One could therefore argue that the A 2A R overexpression reached in our study is beyond the changes found in pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 94%
“…In physiological conditions, A 2A Rs play an important role in fine synaptic tuning (Cunha, 2016): neuronal A 2A Rs regulated NMDA receptors to control synaptic plasticity processes (Rebola et al, 2008;Temido-Ferreira et al, 2018) while astrocytic A 2A Rs control glutamate and GABA uptakes (Lopes et al, 2002;Matos et al, 2012Matos et al, , 2013Cristovao-Ferreira et al, 2013), regulating the excitatory/inhibitory balance. Interestingly, reactive astrocytes have been shown to exhibit adenosine A 2A R upregulation in different neuropathological conditions such as AD, epilepsy, Sandhoff disease, and also in animal models of AD and PD (Orr et al, 2015(Orr et al, , 2018Barros-Barbosa et al, 2016;Zhao et al, 2017;Faivre et al, 2018;Lee et al, 2018;Yu et al, 2008;Hu et al, 2016;Ogawa et al, 2018). However, the pathophysiological impact of such astrocytic A 2A R upsurge remains unclear.…”
mentioning
confidence: 99%
“…As in HD, there was a reduction in A 2A R in regions of high density, such as the striatum, in Alzheimer's disease (AD) [132]. Recently, the selective A 2A R antagonist MSX-3 prevented the development of memory deficits in an AD mouse model without altering hippocampal and cortical gene expression [212].…”
Section: A 2a Ar In the Cnsmentioning
confidence: 99%
“…Moreover, A 2A receptor (A 2A R) antagonists are very safe (Hauser et al, ; Kondo et al, ) and one of them, istradefylline, has been approved in Japan as adjunctive treatment in Parkinson's disease (Jenner, ; Jenner et al, ; Kondo et al, ; Mizuno & Kondo, ; Saki, Yamada, Koshimura, Sasaki, & Kanda, ). It is also noteworthy that A 2A R antagonists afford benefits in the transgenic APPswe/PS1dE9 AD model (Faivre et al, ). For historical reasons related to overexpression in striatal neurons to regulate dopamine neurotransmission, studies on this receptor have focused much more on neurons than in glia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, A 2A receptor (A 2A R) antagonists are very safe (Hauser et al, 2014;Kondo et al, 2015) and one of them, istradefylline, has been approved in Japan as adjunctive treatment in Parkinson's disease (Jenner, 2014;Jenner et al, 2009;Kondo et al, 2015;Mizuno & Kondo, 2013;Saki, Yamada, Koshimura, Sasaki, & Kanda, 2013). It is also noteworthy that A 2A R antagonists afford benefits in the transgenic APPswe/PS1dE9 AD model (Faivre et al, 2018).…”
mentioning
confidence: 99%